PENENTUAN JENIS MINERAL MAGNETIK GUANO DARI GUA SOLEK DAN GUA RANTAI KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA MENGGUNAKAN METODE ISOTHERMAL REMANENT MAGNETIZATION (IRM) - Wilda Febi Rahmadhani (PILLAR OF PHYSICS, 2013)
Based on magnetic susceptibility value from guano of Solek and Rantai Caves, known that guano contain magnetic mineral. Unless the kinds of guano magnetic mineral from both caves didn’t know. Because of that, in this research determined the kinds of guano magnetic mineral, especially the kinds of magnetic mineral from Titanium-Iron Oxide. The method that used to determines magnetic mineral of Titanium-Iron Oxide is Isothermal Remanent Magnetization (IRM) method that detected uses IRM saturation curve and S-Ratio. The sample that detected by IRM saturation curve are guano from Solek and Rantai caves, while the sample that detected by using S-Ratio is guano from Solek cave. Based on IRM saturation curve, known the kinds of magnetic mineral that contain on guano from Solek and Rantai caves are magnetite, and the result of analysis uses S-Ratio is known the kinds of contained mineral magnetic on guano from Solek cave is also magnetite. So, can be indicated that the kind of contained magnetic mineral on guano from Solek and Rantai caves is magnetite. Keywords: Guano, the kinds of magnetic mineral, Isothermal Remanent Magnetization      (IRM), Saturation Curve, S-Ratio